An Abraham Lincoln tribute : featuring woodcuts by Charles Turzak - Turzak, Charles, 1899-1986; Blaisdell, Robert; Berona, David A. (Mineola, New York : Dover Publications, Inc., 2009)
From a humble backwoods cabin to the highest office in the land, this graphic art biography chronicles Abraham Lincoln's path from obscurity to immortality. Its 36 striking woodcuts, each accompanied by a brief caption, depict scenes from the life of the 16th president. Original and imaginative in their stark beauty, these images offer fresh perspectives on the familiar tale of Lincoln's progress from rail-splitter and self-taught prairie lawyer to his role as the Great Emancipator and preserver of the Union. This new edition of Charles Turzak's remarkable book is presented in commemoration of the bicentennial of Lincoln's birth. In addition to a new preface and introduction, it features an appendix with several of Lincoln's famous speeches, letters, and quotations. A keepsake treasure for Civil War buffs and historians, this unique expression of American culture will inspire readers of all ages. - Jacket flap.
Introduction -- "Let us have faith" -- Birth cabin in the woods -- The Lincoln family -- A simple beginning -- Moving to Indiana -- Grave of Nancy Hanks Lincoln -- Indiana home -- Splitting rails -- Borrowing a book -- Moving to Illinois -- Abe at twenty-one -- Down the Mississippi -- Slaves in New Orleans -- Berry-Lincoln store -- Honest Abe -- Lincoln wrestling Jack Armstrong -- Abe and Ann -- Ann Rutledge's grave -- The dual personality -- Lincoln the lawyer -- Making the circuit -- Pleading the case -- Campaigning -- Mary Todd and Lincoln -- Aspirations -- Slavery or freedom -- The debate -- Loyalty to a principle -- "Providence brought me the leadership of this country" -- A prayer for unity -- Deliberation -- Four dark and deliberate years -- The Gettysburg Address -- At the theatre -- The assassination -- "And now he belongs to the ages" -- Supplementary letters and speeches.
Originally published under title: Abraham Lincoln : biography in woodcuts. Chicago : C. Turzak, 1933.
Includes bibliographical references.
Keywords: Lincoln, Abraham, -- 1809-1865 -- Portraits; Wood-engraving, American